2013
DOI: 10.1080/21573727.2013.775943
|View full text |Cite
|
Sign up to set email alerts
|

The trajectory of project management: why EPOS is important

Abstract: This paper welcomes the pluralistic knowledge base represented by EPOS, it being particularly appropriate to our efforts to understand the knowledge needed to manage projects and programs effectively.The paper charts the advances in our thinking about project and program management from the early a-theoretic NASA/DoE days, through a later period reflecting our growing recognition of the importance of managing the Front-End, then to the 'Third Wave' of managing the institutional context, whether internal or ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Morris (2013) and Panagiotakopoulos et al (2016) highlighted a significant gap in the extant literature between formulation and implementation of sustainability standards. Moreover, Morris (2013) and Panagiotakopoulos et al (2016) proposed VSM as an appropriate system modelling technique to address this gap at organizational level. Earlier studies employed SD to analyse different issues related to sustainability (e.g., to analyse the trade‐offs and synergies between sustainability goals, Kopainsky et al, 2015; and for local sustainable development, Cavicchi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Morris (2013) and Panagiotakopoulos et al (2016) highlighted a significant gap in the extant literature between formulation and implementation of sustainability standards. Moreover, Morris (2013) and Panagiotakopoulos et al (2016) proposed VSM as an appropriate system modelling technique to address this gap at organizational level. Earlier studies employed SD to analyse different issues related to sustainability (e.g., to analyse the trade‐offs and synergies between sustainability goals, Kopainsky et al, 2015; and for local sustainable development, Cavicchi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study (Martinez-Lozada & Espinosa, 2022) on viability and sustainability reported rebalancing of organizational structure for improving the effectiveness of corporate sustainability strategy implementation. Morris (2013) and Panagiotakopoulos et al (2016) highlighted a significant gap in the extant literature between formulation and implementation of sustainability standards. Moreover, Morris (2013) and Panagiotakopoulos et al (2016) proposed VSM as an appropriate system modelling technique to address this gap at organizational level.…”
Section: Systems Thinking Approaches and Sustainabilitymentioning
confidence: 99%